The Quality of Educators’ Communication on the Satisfaction of Students’ Guardians and its Impact on Word of Mouth - Faiq Yunianto (LifeSciFi, 2025)
The critical role of interpersonal communication in fostering trust and loyalty among students’ guardians is especially significant in the context of educational marketing. This study aims to analyze the influence of the quality of educator communication on the Word of Mouth (WoM) of students' guardians, with guardian satisfaction as a mediating variable. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 56 guardians of students at Mambaul Hisan Elemetery School, who were selected through simple random sampling. The results showed that the quality of communication had a significant effect on the satisfaction of students' guardians and on WoM directly. In addition, guardian satisfaction also had a significant effect on WoM, and significantly mediated the relationship between communication quality and WoM. The R² value of 0.622 for satisfaction and 0.815 for WoM indicates that the model has high predictive power. This study concludes that good communication quality contributes to creating satisfaction and encouraging voluntary promotion by students' guardians. The practical implications of these findings encourage primary schools to build transparent, consistent, and responsive communication strategies as part of efforts to strengthen the institution's image